IOT System Design for Motion Detection from Remote Monitoring Camera with Telegram Notification to Mobile Phone - M. Auliani Assauri; Helda Yunita; Samsuri; Husnul Ma'ad Junaidi (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
Crime does make people restless, especially if they have to leave their hometown to travel to a faraway place. Becauseo f this concern, humans have begun to create innovations in the field of security, namely a monitoring system using CCTV (Closed Circuit Television) and NVR (Network Video Recorder) as servers and storage devices. However, it tends to be expensive, therefore a security camera monitoring system was created using a Raspberry Pi device which aims to replace the task of CCTV as a security system in a room. The method used is the Waterfall method, one type of application development model that applies sequential and systematic phases. This security system has a motion detection feature that will immediately take pictures and record what is captured by the surveillance camera, then the system will send a notification to the user's Telegram application. In this study, 3 tests were carried out, namely motion detection testing which resulted in overall data being sent, then the second was telegram bot notification testing which resulted in an average loading time of 18.81 seconds, then the last Google Drive auto backup testing which was able to send the most data of 14 images and 14 videos with a time of 69.39 seconds. After several tests, it can be concluded that using a Raspberry Pi device and a web camera can replace CCTV tasks with additional notification features in the Telegram application and auto backup to Google Drive cloud storage.